Lord Mountbatten's The Last Supper: How the British empire botched up the futures of India, Pakistan and Bangladesh - Raman Kumar (Journal of Family Medicine and Primary Care, 2019)
The Lancet, a leading health science journal, has published a political editorial, raising interest in the impact of British colonization on the current status of healthcare, economy and development of the Indian subcontinent. Over two centuries, the East India Company and the British empire siphoned out at least £ 9.2 trillion- or $44.6 trillion; since the exchange rate was $4.8 per pound sterling during much of the colonial period. It is to be noted that the life expectancy of Indians at birth was just 22 years in 1911. Food grain was available, however the purchasing power of ordinary Indians was being squeezed. The per capita annual consumption of food grains went down from 200kg in 1900 to 157kg on the eve of World War II, and further down to 37kg by 1946 (Prof Utsa Patnaik).. The Indian sub-continent has still not come out of the systemic malnutrition inflicted upon the population. Today, just under two billion people, or a quarter of the earth's population, live in India, Pakistan and Bangladesh. The landlocked populations of these countries are known as the black hole of humanity, waiting for ultimate catastrophe- either natural or man-made humanitarian crisis. What happens to these countries now was determined long ago and planned by the British empire when their representatives packed bags and transferred power to the local natives. The partition of India was the most tragic ever human genocide artificially perpetrated in the human history. More than 14 million people were displaced and close to two million people died or went missing. It was the parting gift by the British empire to the people of the Indian sub-continent. This was more tragic than the holocaust. A permanent scar and hatred that would not heal even after a century was created by the British empire. The 200 years of anti-incumbency and hatred against the British was forgotten and used to build a civil war. Enough hatred was fumed between the native population of India and Pakistan. This hatred was further institutionalized between the two countries by having them develop separate militaries. It was a grand exit plan for the empire leaving behind no traces of the crime, while keeping their aura of pride and benevolence intact. After seventy years, it is important to revisit the political circumstances prevailing during the colonial period. It is important for the people India, Pakistan and Bangladesh to think about the future and not be victims of the political game rolled out as an exit plan by the empire.